'Self-Responsibility' and the Politics of Chance: Theorizing the Experience of Japanese Child Welfare. Issue 2 (3rd May 2016) - Goldfarb, Kathryn E.
ABSTRACT: Youth who grow up in Japanese child welfare institutions ('children's homes' or 'orphanages') are socially and structurally marginalized, and many have pasts characterized by neglect and abandonment. In a contemporary context in which young people in Japan are encouraged to think of themselves as agentive, 'self-responsible' subjects, I argue that Japan's child welfare system disproportionately depends on chance in shaping positive or negative outcomes for state wards. Japan's system of care and emancipation from the child welfare system is, I suggest, rooted in a non-empiricist view of experience: despite the fact that most of us depend on our past experiences to guide our expectations for the future, the child welfare system demands that youth leaving care break with a past of dependency and social marginalization to care for themselves with minimal or no state assistance. This article focuses on Tanpopo, a self-help group for people with putatively common experiences receiving care in a child welfare institution. I explore two Tanpopo members' narratives in order to interrogate the assumptions about 'experience' that underlie Japan's child welfare system itself, and the discursive representations of self-responsibility and agentive action in Japan today.